Listening to Unheard Voices in Urban Public Space. The Cases of Ruskin Square and Plaça d'en Baró - Ottaviani, Dorotea; De Marinis, Cecilia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The paper explores the concept of ‘listening to unheard voices’ in the urban environment as a design intention and strategy that contributes to an inclusive and alternative approach to urban public space, considering and promoting the imperatives of caring that such space should deliver to the city and its inhabitants. The ideas discussed in the paper find their background in the research on the concept of care in feminist urbanism and feminist studies in general, and specifically in relation to the model of the Caring City, promoting a city that places care at its centre, and aims to include a wider selection of citizens in the construction of the public good.Through the analysis of two case studies of public spaces designed by solo-women architecture practices, this paper identifies an alternative relational paradigm which gives space to unheard voices in the urban environment through processes of inclusion and participation. The two cases, Plaça d'en Baró in Santa Coloma de Gramenet (Barcelona, Spain), designed by Catalan architectural collective Equal Saree, and Ruskin Square in the London Borough of Croydon (London, UK) designed by British architectural practice muf architecture/art, have implemented the concept of listening to ‘unheard voices’ offering insights into the contribution of women to the urban environment and how it is transformed, shaped, and used.
Keywords: Women Architects; Inclusive City; Caring City; Feminist Practices; Listening Processes